Ethnographic Approaches in Researching Stateless and Undocumented Populations : A Scoping Review - Dayang Hajyrayati, Awg Kassim; Noor Azlan, Mohd Noor (2024)
The scoping review explores the challenges and potential of an ethnographic approach in the study of stateless and undocumented people, shedding light on how these approaches portray the lives and legal invisibility of at-risk and marginalized populations. Stateless individuals, or persons who lack nationality, and undocumented migrants, or people who reside in a country without any formal recognition of their migration status, are two interconnected yet distinct phenomena encountered by many countries worldwide. It is argued that researchers utilizing ethnographic methods, due to their significant focus on detailed and immersive investigations within real-world environments, are uniquely positioned to uncover and address the complex issues that affect these populations. A literature review has been conducted using sources from Google Scholar, Scopus, ProQuest, and Science Direct. Based on the review, ethnography approaches used in analysing statelessness condition not only reveals a widespread instance of socio-legal oppression involving exclusions from healthcare, education, and the legal system, but also captures the social networks, coping mechanisms, and identity struggles that stateless and undocumented individuals experience. To a certain extent, ethnographic studies are useful in addressing the shortcomings of quantitative research, which often fails to recognize the significance of the everyday realities these populations face in their interactions with the state and society. Despite the strengths of ethnographic approaches, this review also discusses methodological limitations, including issues of researcher bias, access to populations, and ethical concerns related to the documentation of illegal or precarious statuses. The review concludes with recommendations for future research, emphasizing the need for ethnographic work that engages directly with policy implications and human rights frameworks, to contribute more effectively to solutions for the stateless and undocumented. By bridging the gap between lived experiences and policy, ethnographic approaches hold the potential to foster more inclusive legal and social reforms.